EFFECTIVENESS OF ONLINE-BASED LEARNING VIA QUIZIZZ DURING THE COVID-19 PANDEMIC - Mastura, Dina Maryana; Wachidi; Riyanto (Corolla International Conference, 2022)
The Covid-19 pandemic requires the Indonesian government to adopt a home-study system policy. This policy is accompanied by instructions for implementing online or remote learning. To facilitate online learning, relevant media are needed, one of which is the Quizizz application media which has educational value so that students can learn innovatively to facilitate the learning process. This research is a quantitative descriptive study aimed at analyzing the effectiveness of online-based learning and the use of Quizizz learning media in English subjects during the covid-19 pandemic. The data collection instrument used an online questionnaire via a google form. The research sample is the X grade students of SMAN 5 Bengkulu Tengah as many as 60 respondents who were selected by simple random sampling technique. The results showed that students' responses to online learning activities were in a good category, while students' responses to Quizizz media were very good. The problem for most students is the limited internet quota and signal problems in the area where students live. Then it was concluded that the online learning system during the Covid-19 pandemic was the most helpful medium for students to achieve learning goals and the qiizizz media was effectively used in the online learning process.